2021
DOI: 10.1021/acscatal.1c01438
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Kinetic Resolution of Carboxylic Esters Catalyzed by Chiral PPY N-Oxides: Synthesis of Nonsteroidal Anti-Inflammatory Drugs and Mechanistic Insights

Abstract: Bifunctional chiral 4-pyrrolidinopyridine (PPY) N-oxides catalyzing the dynamic kinetic resolution of racemic carboxylic esters was reported to construct chiral α-aryl α-alkyl carboxylic esters in up to 93% yield and 99% ee. Several esters of nonsteroidal anti-inflammatory drugs (NSAIDs), including (S)-ibuprofen ester, (S)-ketoprofen ester, (S)-fenaprofen ester, and (S)-flurbinprofen ester, were obtained. Additionally, the drug molecule (S)-naproxen could be achieved by hydrogenation of (S)-naproxen ester. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Moreover, we also attempted the asymmetric versions using chiral DMAP. Unfortunately, after investigating different types of chiral catalysts, 4-pyrrolidinopyridine catalysts 17 showed certain enantiocontrol, constructing chiral product 3a in 33% yield with 68.5 : 31.5 er giving the best result (for more details, please see the ESI†) (Scheme 2B). Most of the catalysts were inactive in cycloaddition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also attempted the asymmetric versions using chiral DMAP. Unfortunately, after investigating different types of chiral catalysts, 4-pyrrolidinopyridine catalysts 17 showed certain enantiocontrol, constructing chiral product 3a in 33% yield with 68.5 : 31.5 er giving the best result (for more details, please see the ESI†) (Scheme 2B). Most of the catalysts were inactive in cycloaddition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Guo, Tian and Xie reported that bifunctional chiral 4-pyrrolidinopyridine N-oxide catalyst 201 promoted the DKR of pentafluorophenol esters 202 through transesterification with diphenylmethanol 155. [58] As presented in Scheme 44, a range of esters reacted with this alcohol in the presence of TEA as a base and 10 mol% of chiral catalyst 201 at 0 °C in trifloromethylbenzene as the solvent to give the corresponding chiral α-aryl α-alkyl carboxylic esters 203 in both uniformly high yields (81-91 %) and enantioselectivities (86-99 % ee). The substrate was supposed to be racemized in the presence of TEA (Scheme 44).…”
Section: Other Reactionsmentioning
confidence: 99%
“…8 Later, our group developed l -prolinamide-derived DMAP- N -oxides as acyl transfer catalysts. 9 Recently, in 2022, our group reported that chiral 4-aryl-pyridine- N -oxides (ArPNO) C6a could be employed as acyl transfer catalysts in the dynamic kinetic resolution of azoles, aldehydes, and anhydrides (Scheme 2a). 10 Through the analysis of the favored transition state obtained by using DFT calculations, the transient azole hemiaminal, a secondary alcohol, could be efficiently acylated with the assistance of H bonding indirectly.…”
Section: Introductionmentioning
confidence: 99%